A preparation method and application of zinc phosphate film
By preparing a nano-scale zinc phosphate film as an interface protective layer on the surface of the zinc negative electrode, the problems of uneven thickness and difficulty in controlling the protective layer in the prior art are solved, and the cycle life and stability of the zinc ion battery are significantly improved.
Patent Information
- Application Number
- CN202211115202.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-09-14
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2042-09-14
AI Technical Summary
The existing artificial protective layer constructed on the surface of zinc negative electrodes has problems such as uneven thickness and difficulty in reaching the nano-level, or difficult to control the thickness of the interface protective layer, resulting in short cycle life and poor stability of zinc ion batteries.
Using a preparation method of zinc phosphate film, a nano-scale zinc phosphate film with controllable thickness is obtained as the interface protective layer of zinc negative electrode by dropping the dodecyl phosphate solution on the surface of zinc sulfate aqueous solution and leaving it stand at room temperature.
By covering a nanoscale thickness Zn3(PO4)2 interface protective layer on the surface of the zinc foil, the corrosion of zinc and the growth of dendrites are suppressed, the cycle life and stability of zinc ion batteries are improved, and the uniform deposition and rapid migration of zinc ions are achieved.
Smart Images

Figure CN115332472B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of metal zinc negative electrodes of aqueous zinc ion batteries. Background Art
[0002] Aqueous zinc-ion batteries have high application value and development prospects in the field of large-scale energy storage. Aqueous zinc-ion batteries have the following advantages: 1) The zinc metal negative electrode has a high theoretical specific capacity (820mAh / g); 2) The natural abundance of zinc is high; 3) The aqueous electrolyte is safe and environmentally friendly; 4) Aqueous zinc-ion batteries are easy to manufacture. However, there are still many problems with aqueous zinc-ion batteries. First, the uneven deposition of zinc during electrodeposition leads to the formation of dendrites. The growing dendrites will pierce the diaphragm, causing a short circuit inside the battery and causing the battery to fail. Secondly, the metal zinc negative electrode will undergo side reactions such as corrosion and hydrogen evolution in the aqueous electrolyte. The side reactions on the interface will cause the zinc to be continuously consumed, which will lead to low coulombic efficiency and short cycle life of the battery. Constructing an artificial protective layer on the surface of the zinc negative electrode for interface optimization can effectively improve the cycle stability and cycle life of zinc-ion batteries. The construction of an artificial interface protective layer can be divided into two methods: ex-situ construction and in-situ construction. The main means of traditional non-in-situ construction of artificial interface protection layer are scraping and spin coating. Although these two methods have the advantages of simple operation and low cost, the thickness of the constructed artificial interface protection layer is uneven and difficult to reach the nanometer level. The uneven protection layer is difficult to control the growth of dendrites, and the thick protection layer will hinder the rapid migration of zinc ions. The in-situ method of constructing an artificial interface protection layer usually introduces additives into the electrolyte to form an interface protection layer on the surface of the zinc negative electrode during the battery cycle. The in-situ method of constructing an interface protection layer has the advantage of self-repair, but it is difficult to control the thickness of the interface protection layer. Summary of the invention
[0003] The present invention aims to solve the problems that the existing artificial protective layer constructed on the surface of zinc negative electrode has uneven thickness and is difficult to reach the nanometer level, or it is difficult to control the thickness of the interface protective layer, and further provides a preparation method and application of zinc phosphate film.
[0004] A method for preparing a zinc phosphate film is carried out according to the following steps:
[0005] Add zinc sulfate aqueous solution to the reaction container, then add dodecyl phosphoric acid / chloroform solution on the surface of zinc sulfate aqueous solution at a dropping speed of 1 μL / s to 3 μL / s, so that the amount of dodecyl phosphoric acid on the air-liquid interface is 0.6 nmol / cm 2 ~1.2nmol / cm 2After the chloroform solvent is completely evaporated, a sodium phosphate aqueous solution is injected into the bottom of the reaction vessel at an injection rate of 0.05 mL / s to 0.15 mL / s, and the solution is allowed to stand at room temperature to obtain a zinc phosphate film at the interface between air and liquid;
[0006] The molar ratio of zinc sulfate in the zinc sulfate aqueous solution to sodium phosphate in the sodium phosphate aqueous solution is 1:(0.5-1).
[0007] Application of zinc phosphate film: zinc phosphate film is used as the interface protection layer of zinc negative electrode in aqueous zinc ion battery.
[0008] The beneficial effects of the present invention are:
[0009] The present invention covers the surface of the zinc foil with a layer of Zn3(PO4)2 interface protection layer of nanometer thickness, and utilizes the hydrophobic organic carbon chain on the surface to block the direct contact between the electrolyte and the zinc negative electrode, thereby inhibiting the corrosion of active zinc and slowing down the side reactions occurring at the interface. Zn3(PO4)2 as an inorganic part can not only inhibit the occurrence of corrosion and side reactions, but also its excellent zinc ion conductivity enables zinc ions to diffuse quickly to the electrode surface, reducing the overpotential of zinc nucleation and growth. The overall interface protection layer is ultra-thin and uniform, ensuring a low zinc ion migration barrier and uniform ion flux, and promoting uniform deposition of zinc ions. Using the zinc foil covered with a protective layer as an electrode and assembling a symmetrical battery, when the area capacity is 1mAh / cm 2 , current density is 1mA / cm 2 The symmetrical battery can be stably cycled 1600 times for 3200 hours at a current density of 50 mA / cm 2 When the area capacity is 1 mAh / cm 2 , current density is 2mA / cm 2 When the battery is 18 mAh / cm2, it can be stably cycled for 4,000 times, with an average coulombic efficiency of 99.81%. 2 , current density is 2mA / cm 2 When the utilization rate of the zinc negative electrode is 61.5%, the battery can be stably cycled for 230 hours. The above data fully demonstrate the commercial application potential of the present invention.
[0010] Therefore, the method of the present invention is simple to operate and low in cost, and can obtain a nanoscale artificial interface protection layer with controllable thickness. The interface protection layer can effectively inhibit the corrosion of the zinc negative electrode and the growth of dendrites, thereby improving the cycle life and stability of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 The actual picture of the Zn3(PO4)2 film prepared in Example 2; a is a culture dish with a diameter of 15 cm, b is a culture dish with a diameter of 9 cm for preparing the Zn3(PO4)2 film, the white substance in b is the precipitate generated by the reaction of zinc sulfate and sodium phosphate when preparing the film, and c is the prepared Zn3(PO4)2 film with a diameter of 9 cm;
[0012] Figure 2 This is an optical microscope image of the Zn3(PO4)2 film prepared in Example 2;
[0013] Figure 3 This is a transmission electron microscope image of the Zn3(PO4)2 film prepared in Example 2;
[0014] Figure 4 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 1;
[0015] Figure 5 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 2;
[0016] Figure 6 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 3;
[0017] Figure 7 This is the full spectrum of the XPS test of the Zn3(PO4)2 film prepared in Example 2;
[0018] Figure 8 1 is a comparison chart of the contact angle test results of zinc sulfate electrolyte with a concentration of 2 mol / L, a is an untreated zinc sheet, and b is a zinc negative electrode covered with an interface protection layer prepared in Example 2;
[0019] Fig. 9 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 1 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0020] Fig.10 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 1 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0021] Fig.11 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 50 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0022] Fig.12 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 50 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0023] Fig.13 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 2 mA / cm 2 And the area capacity is 18mAh / cm 2 Under the condition of , the cycle performance diagram when the zinc negative electrode utilization rate is 61.5%;
[0024] Fig.14 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 2 mA / cm 2 And the area capacity is 18mAh / cm 2 Under the condition of , the cycle performance diagram when the zinc negative electrode utilization rate is 61.5%;
[0025] Fig.15 For Example 2, the aqueous zinc ion Zn||Cu half-cell is operated at a current density of 2 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0026] Fig.16 For comparison, an aqueous zinc ion Zn||Cu half-cell was tested at a current density of 2 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under the condition of ;
[0027] Fig.17 This is a morphology picture of the zinc negative electrode covered with the interface protection layer in Example 2 after being immersed in 1 mL of a 2 mol / L zinc sulfate electrolyte for one week, a is a photo of the zinc sheet after immersion, and b is a scanning electron microscope picture of the surface of the zinc sheet after immersion;
[0028] Fig.18 The morphology of the ordinary zinc sheet after being immersed in 1 mL of 2 mol / L zinc sulfate electrolyte for one week, a is a photo of the zinc sheet after immersion, and b is a scanning electron microscope image of the surface of the zinc sheet after immersion;
[0029] Fig.19 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 20 mA / cm 2 And the area capacity is 1mAh / cm 2 XPS full spectrum of the zinc negative electrode after 20 cycles under the conditions. DETAILED DESCRIPTION
[0030] Specific implementation method 1: This implementation method is a method for preparing a zinc phosphate film, which is carried out according to the following steps:
[0031] Add zinc sulfate aqueous solution to the reaction container, then add dodecyl phosphoric acid / chloroform solution on the surface of zinc sulfate aqueous solution at a dropping speed of 1 μL / s to 3 μL / s, so that the amount of dodecyl phosphoric acid on the air-liquid interface is 0.6 nmol / cm 2 ~1.2nmol / cm 2 After the chloroform solvent is completely evaporated, a sodium phosphate aqueous solution is injected into the bottom of the reaction vessel at an injection rate of 0.05 mL / s to 0.15 mL / s, and the solution is allowed to stand at room temperature to obtain a zinc phosphate film at the interface between air and liquid;
[0032] The molar ratio of zinc sulfate in the zinc sulfate aqueous solution to sodium phosphate in the sodium phosphate aqueous solution is 1:(0.5-1).
[0033] In this specific implementation, the zinc phosphate film is transferred to the zinc foil as an interface protection layer. The thickness of the interface protection layer is controllable and can be prepared on a large area. It is uniform and dense, hydrophobic, and has excellent zinc ion conductivity.
[0034] The beneficial effects of this embodiment are:
[0035] This embodiment covers the surface of the zinc foil with a layer of Zn3(PO4)2 interface protection layer of nanometer thickness, and utilizes the hydrophobic organic carbon chain on the surface to block the direct contact between the electrolyte and the zinc negative electrode, thereby inhibiting the corrosion of active zinc and slowing down the side reactions occurring at the interface. Zn3(PO4)2 as an inorganic part can not only inhibit the occurrence of corrosion and side reactions, but its excellent zinc ion conductivity enables zinc ions to diffuse quickly to the electrode surface, reducing the overpotential of zinc nucleation and growth. The overall interface protection layer is ultra-thin and uniform, ensuring a low zinc ion migration barrier and uniform ion flux, and promoting uniform deposition of zinc ions. Using zinc foil covered with a protective layer as an electrode and assembling a symmetrical battery, when the area capacity is 1mAh / cm 2 , current density is 1mA / cm 2 The symmetrical battery can be stably cycled 1600 times for 3200 hours at a current density of 50 mA / cm 2 When the area capacity is 1 mAh / cm 2 , current density is 2mA / cm 2When the battery is 18 mAh / cm2, it can be stably cycled for 4,000 times, with an average coulombic efficiency of 99.81%. 2 , current density is 2mA / cm 2 When the utilization rate of the zinc negative electrode is 61.5%, the battery can be stably cycled for 230 hours. The above data fully demonstrate the commercial application potential of the present invention.
[0036] Therefore, the method of this embodiment is simple to operate and low in cost, and can obtain a nanoscale artificial interface protection layer with controllable thickness. The interface protection layer can effectively inhibit the corrosion of the zinc negative electrode and the growth of dendrites, thereby improving the cycle life and stability of the battery.
[0037] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the concentration of the zinc sulfate aqueous solution is 10 mmol / L to 50 mmol / L. Other aspects are the same as those of specific embodiment 1.
[0038] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that the concentration of dodecyl phosphoric acid in the dodecyl phosphoric acid / chloroform solution is 0.5 mmol / L to 2.5 mmol / L. The rest is the same as specific implementation method 1 or 2.
[0039] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that the concentration of the sodium phosphate aqueous solution is 5 mmol / L to 50 mmol / L. The rest is the same as specific embodiments 1 to 3.
[0040] Specific implementation mode 5: This implementation mode is different from the specific implementation modes 1 to 4 in that: the mixture is left to stand at room temperature for 7 hours to 24 hours. The rest is the same as the specific implementation modes 1 to 4.
[0041] Specific implementation method 6: Application of zinc phosphate film in this implementation method. The zinc phosphate film is used as an interface protection layer of the zinc negative electrode in an aqueous zinc ion battery.
[0042] Specific embodiment 7: This embodiment is different from specific embodiment 6 in that when the zinc phosphate film is used as the interface protection layer of the zinc negative electrode in the aqueous zinc ion battery, the following steps are specifically performed:
[0043] ①, coating the zinc phosphate film on the zinc negative electrode and drying it to obtain a zinc negative electrode covered with an interface protective layer;
[0044] ②, using the zinc negative electrode covered with the interface protection layer as the negative electrode, assembling the positive electrode, the negative electrode and the separator, adding a zinc sulfate electrolyte with a concentration of 2 mol / L, and obtaining an aqueous zinc ion battery. The rest is the same as the specific embodiment 6.
[0045] Specific implementation eight: This implementation differs from specific implementation six or seven in that the zinc negative electrode described in step ① is obtained by polishing the zinc sheet with sandpaper. The rest is the same as specific implementation six or seven.
[0046] Specific embodiment 9: This embodiment is different from any one of specific embodiments 6 to 8 in that the positive electrode in step ② is a zinc sheet or a copper foil. The rest is the same as specific embodiments 6 to 8.
[0047] Specific embodiment 10: This embodiment is different from any one of specific embodiments 6 to 9 in that the diaphragm described in step ② is a glass fiber membrane or a polypropylene membrane. The rest is the same as specific embodiments 6 to 9.
[0048] The following examples are used to verify the beneficial effects of the present invention:
[0049] Embodiment 1:
[0050] A method for preparing a zinc phosphate film is carried out according to the following steps:
[0051] 12 mL of zinc sulfate aqueous solution was added to a culture dish with a diameter of 9 cm. Then, 25 μL of dodecyl phosphoric acid / chloroform solution was dripped on the surface of the zinc sulfate aqueous solution at a dropping speed of 2 μL / s. After the chloroform solvent was completely evaporated, 8 mL of sodium phosphate aqueous solution was injected into the bottom of the culture dish at an injection speed of 0.1 mL / s. The dish was allowed to stand at room temperature for 7 hours. A zinc phosphate film with a thickness of 19 nm, i.e., a Zn3(PO4)2 film, was obtained at the interface between air and liquid.
[0052] The concentration of the zinc sulfate aqueous solution is 20 mmol / L; the concentration of dodecyl phosphoric acid in the dodecyl phosphoric acid / chloroform solution is 1.8 mmol / L; the concentration of the sodium phosphate aqueous solution is 20 mmol / L;
[0053] Preparation of Zn||Zn symmetric battery:
[0054] ①, using sandpaper to polish the surface of the zinc sheet to make it smooth, then applying a zinc phosphate film on the polished zinc sheet and drying it to obtain a zinc negative electrode covered with an interface protective layer;
[0055] ②, using a zinc negative electrode covered with an interface protection layer as the negative electrode, assembling a positive electrode, a negative electrode and a separator, adding a zinc sulfate electrolyte with a concentration of 2 mol / L, to obtain an aqueous zinc ion battery; the separator is a glass fiber membrane; the positive electrode is a zinc sheet; the aqueous zinc ion battery is an aqueous zinc ion Zn||Zn symmetric battery;
[0056] At a current density of 1 mA cm -2 or 50mA·cm -2and area capacity of 1 mAh cm -2 Under the condition of constant current charge and discharge long cycle test, the aqueous zinc ion Zn||Zn symmetric battery was tested at a current density of 2mA·cm -2 The area capacity is 18 mAh cm -2 Under the condition of , the aqueous zinc ion Zn||Zn symmetric battery was tested with constant current charge-discharge cycle at a discharge depth of 61.5%;
[0057] Preparation of Zn||Cu half-cell:
[0058] ①, using sandpaper to polish the surface of the copper sheet to make it smooth, then applying a zinc phosphate film on the polished copper sheet and drying it to obtain a copper positive electrode covered with an interface protective layer;
[0059] ②, using a copper positive electrode covered with an interface protection layer as the positive electrode, assembling the positive electrode, the negative electrode and the separator, adding a zinc sulfate electrolyte with a concentration of 2 mol / L, to obtain an aqueous zinc ion battery; the separator is a glass fiber membrane; the negative electrode is an ordinary zinc sheet; the aqueous zinc ion battery is an aqueous zinc ion Zn||Cu half-cell;
[0060] At a current density of 2 mA cm -2 and area capacity of 1 mAh cm -2 Under the conditions of long cycle test, the aqueous zinc ion Zn||Cu half-cell was carried out.
[0061] Example 2: This example is different from Example 1 in that: after standing at room temperature for 12 hours, a zinc phosphate film with a thickness of 24 nm is obtained at the interface between air and liquid. Other aspects are the same as Example 1.
[0062] Example 3: This example is different from Example 1 in that: after standing at room temperature for 24 hours, a zinc phosphate film with a thickness of 41 nm is obtained at the interface between air and liquid. Other aspects are the same as Example 1.
[0063] Comparative Experiment 1: The difference between this embodiment and the first embodiment is that: using common zinc sheets as positive and negative electrodes, an aqueous zinc ion Zn||Zn symmetrical battery is obtained; using common copper sheets as positive electrodes and common zinc sheets as negative electrodes, an aqueous zinc ion Zn||Cu half-battery is obtained. The rest is the same as the first embodiment.
[0064] Figure 1This is a photo of the Zn3(PO4)2 film prepared in Example 2; a is a culture dish with a diameter of 15 cm, b is a culture dish with a diameter of 9 cm for preparing the Zn3(PO4)2 film, the white substance in b is the precipitate generated by the reaction of zinc sulfate and sodium phosphate when preparing the film, and c is the prepared Zn3(PO4)2 film with a diameter of 9 cm. Film transfer process: put b into a, fill b with water along the edge of b, and then add water to a until the water surface covers b. At this time, the film will float out of b as the liquid level rises and float on the interface between air and water. Place a solid substrate under the film and lift it up, and the film will be transferred to the solid substrate.
[0065] Figure 2 This is an optical microscope image of the Zn3(PO4)2 film prepared in Example 2; as can be seen from the figure, the protective layer is uniform and continuous.
[0066] Figure 3 This is a transmission electron microscope image of the Zn3(PO4)2 film prepared in Example 2; as can be seen from the figure, the protective layer is dense and continuous, ensuring that it can evenly cover the surface of the zinc negative electrode and adapt to the volume change of the zinc negative electrode without breaking during the battery cycle.
[0067] Figure 4 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 1; as can be seen from the figure, the protective layer is 19 nm thick, the surface is smooth and uniform, and there are basically no impurity particles, which helps zinc ions to be deposited uniformly and quickly through the protective layer.
[0068] Figure 5 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 2; as can be seen from the figure, the thickness of the protective layer is 24nm.
[0069] Figure 6 This is an atomic force microscope image of the Zn3(PO4)2 film prepared in Example 3; as can be seen from the figure, the thickness of the protective layer is 41nm.
[0070] Figure 7 This is the full spectrum of the XPS test of the Zn3(PO4)2 film prepared in Example 2; as can be seen from the figure, the characteristic peaks of Zn3s, Zn2p, O1s and P2p orbitals are clearly present, indicating that the component of the prepared protective layer is determined to be Zn3(PO4)2.
[0071] Figure 8: This is a comparison chart of the contact angle test results of a zinc sulfate electrolyte with a concentration of 2 mol / L, where a is an untreated zinc sheet, and b is a zinc negative electrode covered with an interface protective layer prepared in Example 2; it can be seen from the figure that the contact angle of the protective layer with the 2 mol / L zinc sulfate electrolyte is 112°, which is greater than that of ordinary zinc foil, showing good hydrophobic properties, which helps to prevent the electrolyte from directly contacting the zinc negative electrode and inhibit the occurrence of side reactions.
[0072] Fig. 9 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 1 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; it can be seen from the figure that due to the faster zinc ion transfer kinetics of the protective layer, the Zn||Zn symmetric battery covered with a protective layer exhibits a smaller polarization voltage of 22mV, the faster zinc ion transfer kinetics of the protective layer, and the significant effect of the protective layer on promoting the uniform deposition of zinc ions, the symmetric battery can be stably cycled 1600 times, with a long cycle of 3200 hours.
[0073] Fig.10 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 1 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; It can be seen from the figure that the polarization voltage of the Zn||Zn symmetric battery with ordinary zinc foil is higher than that of the Zn||Zn symmetric battery covered with a protective layer, and due to short circuit caused by dendrite growth, the cycle life is only 300 hours.
[0074] Fig.11 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 50 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; it can be seen from the figure that due to the faster zinc ion transfer kinetics of the protective layer, the Zn||Zn symmetric battery covered with a protective layer exhibits a smaller polarization voltage of 146mV, the faster zinc ion transfer kinetics of the protective layer, and the significant effect of the protective layer on promoting the uniform deposition of zinc ions, the symmetric battery can be stably cycled 12500 times, with a long cycle of 500 hours.
[0075] Fig.12 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 50 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; It can be seen from the figure that the polarization voltage of the Zn||Zn symmetric battery with ordinary zinc foil is significantly higher than that of the Zn||Zn symmetric battery covered with a protective layer, and due to short circuit caused by dendrite growth, the cycle life is only 21 hours.
[0076] Fig.13 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 2 mA / cm 2 And the area capacity is 18mAh / cm 2 Under the condition of , the cycle performance diagram when the zinc negative electrode utilization rate is 61.5%; it can be seen from the figure that the cycle life of the Zn||Zn symmetric battery covered with a protective layer can reach 230 hours, showing its commercial prospects.
[0077] Fig.14 For comparison, an aqueous zinc ion Zn||Zn symmetric battery was used at a current density of 2 mA / cm 2 And the area capacity is 18mAh / cm 2 Under the condition of , the cycling performance diagram when the zinc negative electrode utilization rate is 61.5%; it can be seen from the figure that the Zn||Zn symmetric battery of ordinary zinc foil cannot be cycled normally under high zinc utilization rate.
[0078] Fig.15 For Example 2, the aqueous zinc ion Zn||Cu half-cell is operated at a current density of 2 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; it can be seen from the figure that due to the significant inhibitory effect of the protective layer on the interface side reactions, the Zn||Cu half-cell cycle number reaches 4000 cycles and exhibits a high coulombic efficiency of 99.81%.
[0079] The cycle of the Zn||Cu half-cell is to first discharge the battery at a constant current and then charge it at a constant current. Zinc is deposited on the copper foil during discharge and peeled off from the copper foil during charging. The zinc deposited on the copper foil avoids reacting with the electrolyte under the action of the protective layer. The protective layer can inhibit interfacial reactions. When peeling it back, almost all of the deposited zinc can be peeled back, making the coulombic efficiency close to 100%. The purpose of covering the copper foil with a protective layer is to explore the role of the protective layer in inhibiting interfacial reactions and improving the coulombic efficiency of the battery.
[0080] Fig.16 For comparison, an aqueous zinc ion Zn||Cu half-cell was tested at a current density of 2 mA / cm 2 And the area capacity is 1mAh / cm 2 Long cycle performance diagram under conditions of ; It can be seen from the figure that the coulombic efficiency of the Zn||Cu half-cell without a protective layer suddenly decreases after 110 cycles and cannot be cycled for a long time.
[0081] Fig.17This is a morphology picture of the zinc negative electrode covered with the interface protective layer in Example 2 after being immersed in 1 mL of a 2 mol / L zinc sulfate electrolyte for one week, a is a photo of the zinc sheet after immersion, and b is a scanning electron microscope picture of the surface of the zinc sheet after immersion; it can be seen from the figure that the surface of the zinc sheet covered with the protective layer still has a metallic luster and basically no by-products after being immersed for one week, indicating that the protective layer has a good corrosion inhibition effect on the zinc sheet, and has good adhesion to the zinc foil so that it can be immersed in the electrolyte for one week without falling off and can still function.
[0082] Fig.18 This is a morphology picture of an ordinary zinc sheet immersed in 1 mL of 2 mol / L zinc sulfate electrolyte for one week, a is a photo of the zinc sheet after immersion, and b is a scanning electron microscope picture of the surface of the zinc sheet after immersion. It can be seen from the figure that the surface of the ordinary zinc sheet turns black after being immersed in the zinc sulfate electrolyte for one week, and a large amount of hydroxy zinc sulfate by-products are present.
[0083] Fig.19 For the aqueous zinc ion Zn||Zn symmetric battery of Example 2, the current density is 20 mA / cm 2 And the area capacity is 1mAh / cm 2 The XPS full spectrum of the zinc negative electrode after 20 cycles under the conditions of ; it can be seen from the figure that after the battery cycle, the characteristic peak of the P2p orbital still exists significantly, indicating that the protective layer is still attached to the surface of the zinc sheet after the cycle.
Claims
1. A method for preparing a zinc phosphate film, characterized in that It is carried out in the following steps: Add zinc sulfate aqueous solution to the reaction container, then add dodecyl phosphoric acid / chloroform solution on the surface of zinc sulfate aqueous solution at a dropping speed of 1 μL / s to 3 μL / s, so that the amount of dodecyl phosphoric acid on the air-liquid interface is 0.6 nmol / cm 2 ~1.2nmol / cm 2 After the chloroform solvent is completely evaporated, a sodium phosphate aqueous solution is injected into the bottom of the reaction vessel at an injection rate of 0.05 mL / s to 0.15 mL / s, and the solution is allowed to stand at room temperature to obtain a zinc phosphate film at the interface between air and liquid; The molar ratio of zinc sulfate in the zinc sulfate aqueous solution to sodium phosphate in the sodium phosphate aqueous solution is 1:(0.5-1).
2. The method for preparing a zinc phosphate film according to claim 1, characterized in that The concentration of the zinc sulfate aqueous solution is 10 mmol / L to 50 mmol / L.
3. The method for preparing a zinc phosphate film according to claim 1, characterized in that The concentration of dodecyl phosphoric acid in the dodecyl phosphoric acid / chloroform solution is 0.5 mmol / L to 2.5 mmol / L.
4. The method for preparing a zinc phosphate film according to claim 1, characterized in that The concentration of the sodium phosphate aqueous solution is 5mmol / L to 50mmol / L.
5. The method for preparing a zinc phosphate film according to claim 1, characterized in that Let stand at room temperature for 7 to 24 hours.
6. The use of the zinc phosphate film prepared as claimed in claim 1, characterized in that Zinc phosphate thin films are used as interfacial protective layers for zinc anodes in aqueous zinc ion batteries.
7. Use of the zinc phosphate film according to claim 6, characterized in that When the zinc phosphate film is used as the interface protection layer of the zinc negative electrode in the aqueous zinc ion battery, the following steps are specifically followed: ①, coating the zinc phosphate film on the zinc negative electrode and drying it to obtain a zinc negative electrode covered with an interface protective layer; ②. Use the zinc negative electrode covered with an interface protection layer as the negative electrode, assemble the positive electrode, the negative electrode and the separator, add a zinc sulfate electrolyte with a concentration of 2 mol / L, and obtain an aqueous zinc ion battery.
8. The use of the zinc phosphate film according to claim 7, characterized in that The zinc negative electrode described in step ① is obtained by polishing the zinc sheet smooth with sandpaper.
9. The use of the zinc phosphate film according to claim 7, characterized in that The positive electrode described in step ② is a zinc sheet or a copper foil.
10. The use of the zinc phosphate film according to claim 7, characterized in that The diaphragm described in step ② is a glass fiber membrane or a polypropylene membrane.
Citation Information
Patent Citations
Surface organic phosphoric acid etched composite zinc-philic passive film modified zinc metal negative electrode as well as preparation method and application thereof
CN113964289A
Aqueous zinc ion battery negative electrode material with functional protection layer and preparation method of aqueous zinc ion battery negative electrode material
CN114824236A
Cited By
Method for rapidly preparing zinc phosphate protective layer on zinc negative electrode interface and application
CN121768959A